Financial strain and worry about retirement income adequacy - Magwegwe, Frank M. (Kansas State University, 2020)
Worry about running out of money in retirement (hereinafter referred to as retirement worry) is Americans’ number one financial worry since 2001 (Gallup, 2018a, 2018b, 2019). Increasing frequency and intensity of worry is associated with negative psychological outcomes and impaired cognitive functioning. The overall aim of the present study was to advance the conceptual and empirical understanding of retirement worry. Drawing from worry and stress literature, and theoretically grounded in the Tallis and Eysenck (1994) worry model, the present study utilized partial proportional-odds cumulative logit models and positioned financial strain, financial resources, personal resources, coping strategies (i.e., calculating retirement savings and foregoing medical care), and “coping strategy × financial strain” interactions as key variables in understanding the psychological mechanisms behind retirement worry. Cross-sectional data consisted of survey responses from a nationally representative sample of 13,919 non-retired adults, aged 18 to 64 drawn from the 2018 National Financial Capability Study State-by-State survey. The results surprisingly indicated that financial resources were positively associated with retirement worry while personal resources were negatively associated with retirement worry. Coping strategies had significant but mixed associations with retirement worry. Specifically, calculating retirement savings was negatively associated with retirement worry while foregoing medical care was positively associated with retirement worry. The results underscored the moderating role of coping strategies in the retirement worry process. First, calculating retirement savings exacerbated the effects of financial strain on retirement worry at higher levels of financial strain and mitigated the effects of financial strain on retirement worry at lower levels of financial strain. Second, foregoing medical care exacerbated the effects of financial strain on retirement worry at all levels of financial strain. The conceptual model for retirement worry developed was largely supported which helps to advance the conceptual and empirical understanding of retirement worry. Results from the present study contribute to the literature on retirement worry and financial well-being and should be of interest to policymakers, financial and mental health professionals, companies, and other researchers.
Keywords: Retirement income worry; Financial strain; Financial self-efficacy; Financial mastery; Retirement savings calculation; Foregoing medical care